RESPON TANAMAN PADI MIAU PADA PEMBERIAN PUPUK HORMONIK DESA TENGKAPAK TANJUNG SELOR - Hariyati, Tati; Putra, Marlan Usmani; Aprilo, Yosua (Jurnal Ilmiah Hijau Cendekia, 2024)
Rice is the most common plant cultivated by the Dayak people of North Kalimantan, rice is also sometimes the livelihood of the Dayak people of North Kalimantan in general. Miau rice is mountain rice with a harvest period of five months, the height of the rice can reach an adult's chest, has a fragrant aroma like mountain rice in general, the shape of miau rice grains is slender or slender and the grains are straw yellow, but the problems that exist in this type of rice are quite a lot of empty rice, easily attacked by pests.Plant growth regulators play an important role in controlling biological processes in plant tissue. Its roles include regulating the growth rate of each tissue, accelerating flowering, stimulating root growth, breaking the dormancy period, shortening the harvest period, and increasing production yields. This study aims to determine the correct dosage to correct the deficiencies found in miau rice. The use of the right dosage is believed to improve problems in miau rice such as the amount of empty grain, the harvest age of 6 months with the use of hormones is expected to shorten the harvest life. The research was carried out in Jelarai village, the research was started from March to September 2020. The experiment was arranged in a completely randomized design (CRD). The first dose is 5 ml, the second dose is 10 ml, and the third dose is 15 ml and the comparison is control.